Studi Cross Sectional Hubungan Pemberian ASI Eksklusif dengan Kejadian Stunting - Sari, Padmi Kartika; Isnaeni, Wilya; Sari, Putu Suwita (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2025)
Stunting is a crucial health problem in Indonesia due to its high prevalence of 21.6% in 2022. Stunting is influenced by many factors, one of which is exclusive breastfeeding. This study aims to determine the relationship between exclusive breastfeeding and stunting in children (6-9 months) in the working area of the Labuhan Haji Health Center, East Lombok Regency. This research method is observational analytic with a cross-sectional approach. The sample size was 86, selected using a simple random sampling method. Primary data were obtained from questionnaires on breastfeeding history, environmental sanitation, and complementary feeding history using an interviewer-administered questionnaire. Secondary data were obtained from data at the Labuhan Haji Health Center. Data analysis of both variables was performed using the Chi-Square statistical test. Bivariate test results showed a significant association between exclusive breastfeeding and stunting in children (6-9 months) in the working area of the Labuhan Haji Health Center, East Lombok Regency (p-value = 0,000; PR = 6,932). In Conclusion: There is a significant association between exclusive breastfeeding and stunting in children (6-9 months) in the working area of the Labuhan Haji Health Center, East Lombok Regency.